A threshold‐like effect on the interaction between hydrological connectivity and dominant plant population in tidal marsh wetlands. (26th April 2021) - Liu, Jiakai; Liu, Ying; Xie, Lumeng; Zhao, Shiqiang; Dai, Liyi; Zhang, Zhenming
Abstract: Tidal marsh wetlands in the Yellow River Delta provide valuable eco‐services to the local population and global ecology. However, this area is suffering from serious degradation under the stresses of social development and climate change. Hydrological connectivity, a new framework in hydrology and ecology, has been proposed as the main factor affecting the ecological processes in coastal wetlands; however, its role in hydrology–soil–vegetation interactions remains unclear. In this study, we parametrically quantified the hydrological connectivity in the tidal marsh wetlands and analyzed its relationship with Phragmites australis, one of the dominant species in this area. Our results showed threshold‐like effects on the interaction between hydrological connectivity and P . australis on the plot scale. When biomass is lower than 2.2 kg m −2, the population density and structure size were found to increase with hydrological connectivity. When the biomass is higher than the threshold, the plots disconnected hydrologically because of high water consumption. Compared with soil chemistry, salinity, and water soil content, hydrological connectivity in the surface soil layer is more strongly linked to the plant traits and spatial structure in the tidal marsh wetlands due to the narrow ranges of other variables. Based on the Best on previous study and our analysis, we do not recommend dense plantation of P . australis, especially near the freshwater sources in the tidal marsh, because of its high reproduction ability and competitive nature, which may cut the freshwater connectivity off, lowering the richness of plant species and habitat diversity.